ANALISIS ASPEK PEMASARAN, SUMBER DAYA MANUSIA, DAN PRODUKSI PADA UMKM DIMSUM 86 PUJASERA SALATIGA - Dwi Nurrahmawati; Diana Wulandari; Tea Martina Laores; Mokhamad Khukaim Barkhowa (Andromeda : Jurnal Manajemen dan Bisnis Syariah, 2026)
This research was conducted due to the discrepancy between the positive image of Dimsum 86 Pujasera Salatiga, which received a positive response from customers, and several operational issues that still exist in the service and management of the business. This study aims to analyze the marketing, workforce, and production processes at the Dimsum 86 Pujasera Salatiga, as well as provide suggestions for improvements that can help improve the progress of the business. This research uses a descriptive qualitative approach, where data is collected through interviews, observations, and document checking. Data accuracy is tested using source triangulation and technical triangulation methods. The research shows that the marketing aspect is supported by consistent good product quality, low prices, and the use of social media as a means of advertising. The human resources aspect shows the existence of clearly divided tasks, the ability to provide good customer service, and smooth communication with consumers. Meanwhile, the production aspect is supported by the implementation of the First In First Out system, maintaining the cleanliness of the production area, and following standard operating procedures in every stage of production. Potential managerial implications include creating a sales promotion program, developing an employee assessment and reward system, and digitizing inventory records to improve business management effectiveness. Overall, Dimsum 86 Pujasera Salatiga has a relatively good marketing, human resource, and production environment and has the potential for continued growth if operational management is improved.